Functional impairment of human myeloid dendritic cells during Schistosoma haematobium infection. - Bart Everts; Ayola A Adegnika; Yvonne C M Kruize; Hermelijn H Smits; Peter G Kremsner; Maria Yazdanbakhsh (PLoS Neglected Tropical Diseases)
Chronic Schistosoma infection is often characterized by a state of T cell hyporesponsiveness of the host. Suppression of dendritic cell (DC) function could be one of the mechanisms underlying this phenomenon, since Schistosoma antigens are potent modulators of dendritic cell function in vitro. Yet, it remains to be established whether DC function is modulated during chronic human Schistosoma infection in vivo. To address this question, the effect of Schistosoma haematobium infection on the function of human blood DC was evaluated. We found that plasmacytoid (pDC) and myeloid DC (mDC) from infected subjects were present at lower frequencies in peripheral blood and that mDC displayed lower expression levels of HLA-DR compared to those from uninfected individuals. Furthermore, mDC from infected subjects, but not pDC, were found to have a reduced capacity to respond to TLR ligands, as determined by MAPK signaling, cytokine production and expression of maturation markers. Moreover, the T cell activating capacity of TLR-matured mDC from infected subjects was lower, likely as a result of reduced HLA-DR expression. Collectively these data show that S. haematobium infection is associated with functional impairment of human DC function in vivo and provide new insights into the underlying mechanisms of T cell hyporesponsiveness during chronic schistosomiasis.